Dasholi Gram Swarajya Mandal / by Ramesh Pahari ; translators, Navin Juyal & Ravi Chopra - Pahari, Ramesh (The Mandal, 1997)
On the programmes and activities of the Dasholi Gram Swarajya Mandal for the rural development of Chamoli District.